FEED UTILIZATION, GROWTH AND BREEDING OF LIVE BEARING ORNAMENTAL FISH RED PLATY XIPHOPHORUS MACULATES IN RELATION TO DIFFERENT FEEDS - RAJAN, M.R.; MANOHARI, A. ANGELINE (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2011)
The present study deals with the feed utilization, growth and breeding of live bearing ornamental fish red platy Xiphophorus maculates in relation to different feeds. One commercial feed and two different feeds were prepared using earthworm meal, fish meal, ground nut oil cake. Wheat flour and tapioca powder. Feed utilization parameters such as feed consumption, feed conversion efficiency, feed conversion ratio, growth, percentage growth, relative growth rate, assimilation. metabolism, gross and net growth efficiency and breeding was studied in red platy for a period of 60 days. The feed consumption, feed conversion efficiency and ratio, growth and percentage growth, assimilation, metabolism, grOSS and net growth efficiency were higher in feed III containing earthworm meal. The relative growth rate is higher in feed II. The number of young ones produced by red platy was higher in feed III. The spawning frequency of red platy was 56, 55 and 54 for feed I, III and III, respectively.